1971
DOI: 10.1002/jsfa.2740220406
|View full text |Cite
|
Sign up to set email alerts
|

Bread staling: I.—Experimental study

Abstract: Starting with a typical baker's dough, a model system was constructed in order to examine whether moisture re-distributed itself bet ween the two principal components, gluten and starch, of crumb during ageing.It was estimated that up to 30 % of the moisture associated with thegluten fraction, migrated to the starch during I20 h of storage of the baked system at 2J"c. The rate of migration decreased upproximately exponentially with time. Moisture from the gluten was also found to migrate to the starch during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…The first distribution has been assigned to water that exhibits strong interactions with gluten and starch (Assifaoui et al, 2006;Engelsen et al, 2001;Kim & Cornillon, 2001;Ruan et al, 1999). Such a statement is rather ambiguous since it is documented in the literature that the molecular interactions of gluten water are distinct from those with starch (Li, Dickinson, & Chinachoti, 1996;Umbach, Davis, Gordon, & Callaghan, 1992;Wang, Choi, & Kerr, 2004;Wilhoft, 1971;Wynne-Jones & Blanshard, 1986). Moreover, as is shown in the inset of Fig.…”
Section: Water Dynamics Of Thawed Flour-water Mixtures Probed By Nmrmentioning
confidence: 91%
“…The first distribution has been assigned to water that exhibits strong interactions with gluten and starch (Assifaoui et al, 2006;Engelsen et al, 2001;Kim & Cornillon, 2001;Ruan et al, 1999). Such a statement is rather ambiguous since it is documented in the literature that the molecular interactions of gluten water are distinct from those with starch (Li, Dickinson, & Chinachoti, 1996;Umbach, Davis, Gordon, & Callaghan, 1992;Wang, Choi, & Kerr, 2004;Wilhoft, 1971;Wynne-Jones & Blanshard, 1986). Moreover, as is shown in the inset of Fig.…”
Section: Water Dynamics Of Thawed Flour-water Mixtures Probed By Nmrmentioning
confidence: 91%
“…Bushuk and Winkler (1957) reported that water is bound more to starch than to gluten, due to the higher water sorption capacity of starch. Through separation of the components of dough and measuring the moisture content of each component during baking and storage, Willhoft (1971) suggested that there is more water associated with the gluten than with the starch in the dough, and that the water moves from the gluten to the starch during conventional baking. Using differential thermal analysis (DTA) and differential scanning calorimetry (DSC), several researchers found that the bound water content in dough was independent of flour protein content, added chemicals, amount of damaged starch and mixing time (Davis & Webb, 1969;Daniels, 1975;Bushuk & Mehrotra, 1977a-c).…”
Section: Introductionmentioning
confidence: 99%
“…Stone (8) noticed that the crisp crust became softer and more leathery during staling, probably owing to migration of moisture from the crumb, or possibly owing to absorption of moisture from the atmosphere (9). Willhoft (6) and Breaden and Willhoft (5) reported that gluten undergoes a transformation resulting in the release of water (once a part of the gluten structure) which becomes absorbed by retrograding starch. Others suggest that water is expelled from the starch matrix due to retrogradation (10).…”
Section: Introductionmentioning
confidence: 99%